2015
DOI: 10.14310/horm.2002.1572
|View full text |Cite
|
Sign up to set email alerts
|

Study of common variants of the apolipoprotein E and lipoprotein lipase genes in patients with coronary heart disease and variable body mass index

Abstract: OBJECTIVE:In the present study, we evaluated the influence of lipoprotein lipase (LPL) and apolipoprotein (apo) E polymorphisms on lipid concentrations of 178 Greek men of similar age with coronary heart disease (CHD), but varying body mass index (BMI). DESIGN: Patients were divided according to their BMI (in kg/m²) into three groups: lean (BMI=20-24.9), overweight (BMI=25-29.9), and obese (BMI ≥30). Polymorphisms of LPL (HindIII, S447X) and apo E (ε2, ε3, ε4), and lipid parameters were studied. RESULTS: There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Moreover, the rs320 (Hindlll) polymorphism was cross‐sectional associated with higher TG levels and lower HDL levels in the presence of visceral obesity. [ 23 ] Furthermore, the AA+AG genotype of the rs2197089 polymorphism was associated with decreased TG concentration. In this study, smoker participants with the minor allele A had a higher LPL activity and therefore increased HDL concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the rs320 (Hindlll) polymorphism was cross‐sectional associated with higher TG levels and lower HDL levels in the presence of visceral obesity. [ 23 ] Furthermore, the AA+AG genotype of the rs2197089 polymorphism was associated with decreased TG concentration. In this study, smoker participants with the minor allele A had a higher LPL activity and therefore increased HDL concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that in Iranian children and adolescents, carriers of T allele of rs320 polymorphism are associated with lower TG and LDL-C and higher TC and HDL-C (24). Other studies showed that in healthy-weight men with coronary heart disease, the rs320 polymorphism alone might impress the HDL-C concentration, in contrast to rs328 alone, which has no influence on any lipid parameters (53).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, LPL is involved in the atherogenesis since it influences the interaction between atherogenic lipids and the surface of endothelial cells of arterial vessel walls [11]. Changes of LPL activity may occur in some pathophysiological processes related to obesity, diabetes, chylomicronemia and atherosclerosis [12].…”
Section: Lipoprotein Lipase (Lpl)mentioning
confidence: 99%